2021
DOI: 10.21037/qims-20-1310
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypothyroidism on referential background metabolic activity on 18F-FDG PET/CT

Abstract: Background: Background uptake activity is used as a reference to assess treatment response by positron emission tomography-computed tomography (PET/CT) with 2-deoxy-2- [F-18]fluoro-D-glucose ( 18 F-FDG).Prior studies have reported decreased liver and increased muscle 18 F-FDG uptake in patients with hyperthyroidism. We hypothesized that hyperthyroidism and hypothyroidism might have inverse effects on 18 F-FDG uptake on PET/CT. Methods: We recruited 36 patients with hypothyroidism and 36 age and gender-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The criteria for hypothyroidism in this study were specified as increased TSH and decreased FT4 levels, which are also the diagnostic criteria of clinical hypothyroidism. Although examining patients with more severe hypothyroidism may be more favorable to corroborate our findings, as confirmed in the study by Yang et al [15], to avoid statistical bias, we excluded patients with severe medically induced hypothyroidism due to thyroidectomy or iodine treatment. Our study continues to show that even with mild hypothyroidism, the slower the liver tissue SUV mean decreases while clinical symptoms are present, the greater the SUV mean in delayed imaging.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The criteria for hypothyroidism in this study were specified as increased TSH and decreased FT4 levels, which are also the diagnostic criteria of clinical hypothyroidism. Although examining patients with more severe hypothyroidism may be more favorable to corroborate our findings, as confirmed in the study by Yang et al [15], to avoid statistical bias, we excluded patients with severe medically induced hypothyroidism due to thyroidectomy or iodine treatment. Our study continues to show that even with mild hypothyroidism, the slower the liver tissue SUV mean decreases while clinical symptoms are present, the greater the SUV mean in delayed imaging.…”
Section: Discussionsupporting
confidence: 73%
“…tissue, which in turn leads to an increase in SUV mean and a slower decrease in liver tissue SUV mean with time. Indeed, a previous study [15] suggested that TSH can have an effect on the SUV value of normal liver tissue, but that study was not performed under tumor load. In our study, we discuss the SUV mean of normal liver tissue in hypothyroid patients under CRLM load, showing that FDG uptake by normal liver tissue in hypothyroid patients is still affected even under conditions of tumor load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that thyroid function can impact the metabolic activity of various tissues, as evidenced in 18 F-FDG PET/CT scans [6]. Under physiological conditions, the pituitary gland shows little uptake of 18 F-FDG; incidental findings of pituitary hypermetabolism are unusual, with a reported frequency of 0.8% [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%